Learning Strategies at SD Muhammadiyah 2 Krian During the Covid-19 Pandemic - Atim Alfin Setyawan; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study aims to provide an overview of the strategies implemented by SD Muhammadiyah 2 Krian in the learning process during the Covid-19 pandemic. The method used in this research is descriptive qualitative method. The data collection techniques in this study were through interviews, documentation and observation. During the Covid-19 pandemic, SD Muhammadiyah 2 Krian implemented an online learning policy, in accordance with the instructions issued by the Minister of Education and Culture Nadiem Makarim through Circular Number 4 of 2020 concerning Implementation of Educational Policies in the emergency period of the spread of the Corona virus. Online learning is carried out in order to reduce the spread of covid-19. During the implementation of online learning, SD Muhammadiyah 2 Krian experienced several obstacles in various ways, such as limited devices, limited internet networks, and limited understanding of subject matter by students. Behind all the obstacles experienced, SD Muhammadiyah 2 Krian provides a solution called the consultation class. This consultation class is intended for students who have problems understanding the subject matter.